Material Construction of Care Workers’ Identity - Laulainen, Sanna; Hujala, Anneli (Nordic Journal of Working Life Studies, 2016)
This article takes a critical look at the unconscious and unnoticed effects of materiality on care workers’ identity. The data was collected through nonactive role-playing using written accounts, in which the respondents described how they felt about working in fictitious ‘good’ or ‘bad’ elderly care homes. The data was analyzed with rhetorical analysis. Five different identity strategies were identified in the accounts. Strong professional identity was defended by downplaying the significance of materiality. Adjustment and passive compliance were used to adjust to physical shortcomings of the work environment. A ‘rebellion’ was described as an extreme course of action to resolve the contradiction between good care and poor facilities. At its best, the materiality of care homes, in particular homelikeness, seemed to support professional identity. These identity strategies illustrate how care workers balance between the physical realities of care homes and the requirements of the ethos of care, which are often incompatible with each other. It is crucial that managers as well as workers themselves recognize and acknowledge these connections affecting motivation and commitment to care work. Investments in better environments could be one way to improve the image and the attractiveness of the care branch and relieve the recruitment problems.